Identity and conscience: a critique of bourgeois idea of citizenship - Karataş, İbrahim Halil (İstanbul Bilgi Üniversitesi, 2021)
ABSTRACT: This study intends to examine the bourgeois or liberal-democratic idea of citizenship by concentrating on its two main categories: 'General Will' and 'Public Opinion.' We discuss these two categories by clarifying their relations with 'Identity' and 'Conscience.' Firstly, the results of the human-citizen identity that liberal democratic citizenship aims to establish through the general will category is touched upon. This identity implies the construction of a 'universal self-consciousness,' which means associating the moral subject and the political subject under the concept of the citizen subject. Furthermore, a critique of the idea of liberal democratic citizenship is presented based on Etienne Balibar's assessments on distinctions such as activepassive citizen and human rights-citizen rights. Secondly, the study focuses on the role of the reduction of conscientious judgment to opinion in the formation of the Public Opinion category. It is pointed out that the category of modern public opinion is designed as an organ devoted to the spread of public virtues, to equip generations with these virtues, and to ensure that citizens reach the ideal of the public use of reason through education. It is claimed that the category of public opinion is the rationality of bourgeois publicity. In order to justify this claim, an evaluation of the concept of 'instrumental reason' is made. The thesis to be put forward in this study is that the relevant categories of liberal democratic citizenship thought have inherent contradictions, and these contradictions are rooted in the identifying thought in the Adornian sense. The crisis of citizenship in the 21st century is understood as a result of this thought. The last part of the study is framed as an introduction to the evaluation of the consequences of the crisis of citizenship. The situation of the citizen subject is analyzed in terms of the dissolution of social citizenship and the category of public opinion. Then, it is expressed that the failure of the attempt to identify the political subject with the moral subject has gave rise to a movement for the citizen subject, a movement that is called the return to morality. Finally, it is argued that this movement means the replacement of the collapsing universal identity by conscience. The ideological character of the concept of conscience gained as a result of these developments is elaborated.

ÖZET: Bu çalışma, Burjuva ya da liberal demokratik yurttaşlık fikrini, onun 'Genel İrade' ve 'Kamuoyu' olarak adlandırılan iki ana kategorisi üzerinde yoğunlaşarak incelemeyi amaçlamaktadır. Bu iki kategoriyi, ‘özdeşlik ve 'vicdan' kavramlarıyla bağlantılandırarak değerlendirmek suretiyle tartışacağız. İlk olarak, liberal demokratik yurttaşlık düşüncesinin genel irade kategorisi vasıtasıyla tesis ettiği insan-yurttaş özdeşliğinin yarattığı sonuçlar üzerinde durulacaktır. Bu özdeşlik, bir ‘evrensel kendilik bilinci’ne işaret eder. Ahlaki özne ile siyasi öznenin yurttaş özne konsepti altında birleştirilmesi anlamına gelmektedir. Yine, Liberal demokratik yurttaşlık düşüncesinin eleştirisi; Etienne Balibar'ın aktif-pasif yurttaş, insan hakları-yurttaş hakları gibi ayrımlar üzerine yaptığı değerlendirmelere bağlı kalınarak sunulacaktır. İkinci olarak, kamuoyu kategorisinin oluşumunda vicdani yargının kanıya indirgenmesinin rolü üzerinde durulacaktır. Modern kamuoyu kategorisinin kamusal erdemlerin yaygınlaşmasını, nesillerin bu erdemlerle donatılmasını, yurttaşların eğitim yoluyla aklın kamusal kullanımı idealine ulaştırılmasını sağlamaya ayrılmış bir organ olarak kurgulandığına işaret edilecektir. Kamuoyu kategorisinin burjuva kamusallığın rasyonalitesi olduğu iddia edilecektir. Bu iddiayı temellendirmek için ‘araçsal akıl’ kavramı üzerinden bir değerlendirme yapılacaktır. Bu çalışmada öne sürülecek tez, Liberal demokratik yurttaşlık düşüncesinin ilgili kategorilerinin içkin çelişkilere sahip olduğu ve bu çelişkilerin temelinde de Adorno'cu anlamda bir özdeşleştirici düşüncenin yattığıdır. Yurttaşlığın 21. yüzyılda yaşadığı kriz bu düşüncenin sonucu olarak kavranacaktır. Son olarak, çalışmanın son bölümü yurttaşlığın krizinin yarattığı sonuçların değerlendirilmesi yönelik bir giriş olarak kurgulanmıştır. Yurttaş öznenin durumu, kamuoyu kategorisi ile sosyal yurttaşlığın çözülmesi açısından değerlendirilecektir. Bunun ardından, siyasi özneyle ahlaki özneyi özdeş kılma girişiminin başarısızlığının yurttaş özne açısından bir ahlaka dönüş hareketine yol açtığı ifade edilecektir. Bu hareketin, çöken evrensel özdeşliğin yerini vicdanın alması anlamına geldiği iddia edilecektir. Kavramın, bu gelişmeler neticesinde kazandığı ideolojik nitelik üzerinde durulacaktır.
Özdeşlik ve vicdan: burjuva yurttaşlık düşüncesinin bir eleştirisi
Keywords: General Will; Public Opinion; Identity; Conscience; Instrumental Reason; Genel İrade; Kamuoyu; Özdeşlik; Vicdan; Araçsal Akıl